2016
DOI: 10.1177/2050640615604774
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and safety of endoscopic resection in the management of subepithelial lesions of the stomach

Abstract: Background: Gastric subepithelial tumors represent a diagnostic and therapeutic challenge, given their histologic heterogeneity and potential malignant behavior. Objective: The objective of this article is to evaluate the interest, efficiency and safety of endoscopic resection for subepithelial gastric lesions of size <20 mm. Methods: We conducted a single-center retrospective study in a tertiary care center. Results: A total of 33 lesions (10 malignant/23 benign lesions) were studied. Mean histological size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Several other case series have recently reported successful ESD for various gastric submucosal tumors such as ectopic pancreas, ectopic spleen, leiomyoma, and gastrointestinal stromal tumor (GIST) [23, 24]. In another case series from France, the authors reported successful resection of 33 submucosal lesions in the stomach for lesions <20 mm, with the majority of lesions being resected by ESD [25]. In this study, 6 lesions dissected were submucosal in origin.…”
Section: Discussionmentioning
confidence: 63%
“…Several other case series have recently reported successful ESD for various gastric submucosal tumors such as ectopic pancreas, ectopic spleen, leiomyoma, and gastrointestinal stromal tumor (GIST) [23, 24]. In another case series from France, the authors reported successful resection of 33 submucosal lesions in the stomach for lesions <20 mm, with the majority of lesions being resected by ESD [25]. In this study, 6 lesions dissected were submucosal in origin.…”
Section: Discussionmentioning
confidence: 63%
“…Several authors have described the usefulness of ESD for small and asymptomatic gastric submucosal tumors ( 16 , 17 ). It was recently reported that endoscopic resection of subepithelial tumors of the stomach has a high success rate with few adverse events ( 18 ). In the present case, EUS suggested that the tumor was located within the submucosal layer without involvement of the muscular layer.…”
Section: Discussionmentioning
confidence: 99%
“…Weak recommendation, low quality evidence) more reliable determination of the mitotic count and Ki67 labeling index compared with EUS-guided sampling [110]. However, such aggressive techniques that use a knife or a snare to expose the SEL surface for biopsy sampling are inadequate for deep SELs (e. g., fourth EUS layer with protrusion to the peritoneal side) and are neither standardized nor widespread [111,112].…”
Section: Recommendationmentioning
confidence: 99%